Policy discourse and the paradigm shift in reproductive health in Bangladesh - Ghafur, Tehmina (Cambridge Scholars Publishing, 2017)
The reproductive health care program of Bangladesh is still striving to address the very basic reproductive health issues of its people. Reproductive health services here still confronting issues surrounding 'availability'. Equality issues like 'accessibility' to, and 'quality' of services are far away from the reach of the majority of people. This book analyses the policy discourses and the paradigm shift relating to reproductive health care in Bangladesh. It explores the extent to which the policy frameworks reflect a paradigm shift towards a rights-based reproductive health program. In so d.